Role of Lysine-specific Demethylase 1 and Its Small Molecule Inhibitors in Glioblas-toma Multiforme Therapy - Mitra R.; Ayyannan S.R. (My University, 2025)
Glioblastoma multiforme (GBM) is among the most critical and aggressive carcinomas of CNS, character-ised by poor prognosis, low survival rate and difficult clinical correlations. Current treatment opportunities have proved to be insufficient due to high chemoresistance and relapse of the disease with enhanced malignancy. Molecular diagnostics and epigenetic profiling of GBM have discovered several signaling pathways and cellular mediators, which play key roles in triggering GBM phenotypic manifestations via somatic and genetic aberrations and recruitment of GBM stem-like cells (GSCs). Lysine specific demethylase 1 (LSD1), a flavin-containing oxidoreductase encoded by the KDM1A gene and containing the unique CoREST component, is an important histone-modifying enzyme belonging to the histone demethylase (KDM) subfamily and is responsible for master regulation of several signaling pathways in glioma cells. Pharmacological inhibition of LSD1, either individually or in a dual-targeted approach, is a logical strategy for the management of GBM. The current review discusses the role of LSD1 in various epigenetic modulations in differentiated glioma cells and GSCs. The 2D and 3D structural similarities/dissimilarities between LSD1 and MAOs have been analysed and presented along with a detailed discussion on different chemical classes of small molecule LSD1 inhibitors (both standalone and hybrid pharmacophores) that have shown promise in GBM chemotherapy. © 2022 Bentham Science Publishers.